Management of lettuce rot caused by Fusarium oxysporum f. sp. lactucae in hydroponically grown crop using microbial consortia - PRADIP KUMAR BORAH, PARVEEN KHAN*, LOHIT CHANDRA BORA and (Indian Phytopathology, 2017)
Hydroponics or growing plants on mineral nutrient solutions without soil has many advantages, as the system has higher water and fertilizer use efficiency, and crop encounters very low pest and disease incidence which inevitably check the requirement of plant protection chemicals. However, recently few of the diseases caused by commonly observed pathogens in conventional soil based system have also been detected in hydroponic culture, bringing a serious risk to hydroponic crop production. The present investigation was made to assess the effectiveness of bio-intensive management of Fusarium rot of lettuce incited by Fusarium oxysporum f. sp. lactucae (FoL) under hydroponic culture tank system in Assam during 2014-2016. Three rhizosphere inhabiting microbial agents, viz., Trichoderma harzianum, Bacillus thuringiensis and Pseudomonas fluorescens were tested singly as well as in consortia against the pathogen. The microbial agent, T. harzianum exhibited comparatively high antagonistic activity showing highest suppression of FoL in vitro. In hydroponic tanks, T. harzianum applied as root application, showed lowest root infection (15.39%), leaf infection (18.09%) and overall lower disease incidence (17.29%) with highest crop growth attributes and yield. This was followed by treatment with consortia of T. harzianum and B. thuringiensis. The highest root infection (85.08%), leaf infection (70.02%), rot incidence (80.97%) and lowest yield (30.00g/plant) have been recorded in untreated lettuce plants in control tanks.